RESPONSABILIDADE SOCIAL E CIDADANIA EMPRESARIAL EM MÁQUINAS-FERRAMENTAS: CASO DAS TUPIAS - Schneider, Andresa; Endruweit, Andreas A. B.; Eckhardt, Moacir; Ribeiro, Luis F. M.; Sackser, Gilberto; Duarte, Luiz C. S. (Salão do Conhecimento, 2013)
Resumo